Kurikulum Pendidikan Agama Kristen dalam Membangun Nilai-Nilai Moral: Sebuah Kajian Pustaka - Melvana Evriani Hutagalung; Ordekoria Saragih (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Christian Religious Education (PAK) has a very important role in building students' moral values, especially in the context of education in Indonesia which is implemented based on the Independent Curriculum. This research aims to examine how the Christian Religious Education Curriculum contributes to the formation of students' moral values. This literature review explores various literature that discusses the basic concepts and principles of PAK as well as the implementation of this curriculum in moral education. Based on literature analysis, it can be concluded that the Independent Curriculum provides space for deepening moral values through a more flexible and contextual approach. In this curriculum, teachers are expected not only to convey religious teaching material but also to instill Christian values which include love, justice, forgiveness and social responsibility to students. Project-based learning, reflection, and collaboration in the classroom are some of the main strategies proposed to build student character according to the teachings of the Bible. Thus, PAK through the Merdeka Curriculum plays a significant role in forming students' moral character of quality and noble character.